2012
DOI: 10.1002/jor.22247
|View full text |Cite
|
Sign up to set email alerts
|

An orthopedic tissue adhesive for targeted delivery of intraoperative biologics

Abstract: Tissue adhesives can bind together damaged tissues and serve as tools to deliver and localize therapeutics to facilitate regeneration. One emerging therapeutic trend in orthopedics is the use of intraoperative biologics (IOB), such as bone marrow (BM) and platelet-rich plasma (PRP), to stimulate healing. Here, we introduce the application of the biomaterial chondroitin sulfate succinimidyl succinate (CS-NHS) to deliver IOB in a hydrogel adhesive. We demonstrate the biomaterial's ability to bind various tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 52 publications
1
41
0
1
Order By: Relevance
“…For instance, the growth factors released from PRF following its activation can be immobilized by the addition of an acidic gelatin material with an isoelectric point of 5.0; the physicochemical interplay substantially alters the growth factors' kinetic profile because release depends on hydrogel degradation [622]. Similar strategies have been reported using CS [627], alginate [623], collagen [624] or PCL-tricalcium phosphate (TCP) composites [625] as the underlying biomaterials. Interestingly, via a heparin-binding delivery system, the incorporation of exogenous growth factors or other bioactive molecules into its mesh structures may additionally improve the functionality of PRF as a scaffolding material [438].…”
Section: Formulations Enriched With Endogenous Growth Factorsmentioning
confidence: 99%
“…For instance, the growth factors released from PRF following its activation can be immobilized by the addition of an acidic gelatin material with an isoelectric point of 5.0; the physicochemical interplay substantially alters the growth factors' kinetic profile because release depends on hydrogel degradation [622]. Similar strategies have been reported using CS [627], alginate [623], collagen [624] or PCL-tricalcium phosphate (TCP) composites [625] as the underlying biomaterials. Interestingly, via a heparin-binding delivery system, the incorporation of exogenous growth factors or other bioactive molecules into its mesh structures may additionally improve the functionality of PRF as a scaffolding material [438].…”
Section: Formulations Enriched With Endogenous Growth Factorsmentioning
confidence: 99%
“…This unique hydrogel-biomolecule composition was recently introduced by Simson et al who showed that a CS-NHS adhesive hydrogel is a promising delivery tool for intraoperative biologics (such as PRP and bone marrow) in orthopedic applications [113]. …”
Section: Hydrogels and Spongesmentioning
confidence: 99%
“…One of the most novel aspects of this material is the presence of photoreactive groups, which allows fo r instant curing using UV light. This material had been further developed to include platelet rich plasma (PRP) in the bio-glue solution ( Figure 4C) (192,192). PRP has become a popular injection therapy for degrading articular joints due to the presence of growth factors within PRP that have been implicated in chondrogenesis (193,193).…”
Section: Engineering the Transition Zonementioning
confidence: 99%